Kiss of death - Caine, Rachel (New York, N.Y., U.S.A. : Signet, 2010)
Vampire musician Michael Glass has attracted the attention of a big-time producer who wants to cut a demo and play some dates. Which means that Michael will have to enter the human world. For this, he's been assigned escorts that include both a dangerous immortal as well as Michael's all -too=human friends. And with that mix of personalities, this is going to be a road trip from hell.
Keywords: Vampires -- Juvenile fiction; Musicians -- Juvenile fiction; Missing persons -- Juvenile fiction; Private investigators -- Juvenile fiction; Horror tales; University towns -- Juvenile fiction; Vampires -- Fiction; Musicians -- Fiction; Missing persons -- Fiction; Private investigators -- Fiction; Horror stories